The Spanish Diplomat's Secret: Captain Jim and Lady Diana Mysteries #3 - March, Nev, 1967- (New York : Minotaur Books, 2023)
"Captain Jim Agnihotri and his wife Lady Diana Framji are embarking to England in the summer of 1894. Jim is hopeful the cruise will help Diana open up to him. Something is troubling her, and Jim is concerned. On their first evening, Jim meets an intriguing Spaniard, a fellow soldier with whom he finds an instant kinship. But within twenty-four hours, Don Juan Nepomuceno is murdered, his body discovered shortly after he asks rather urgently to see Jim. When the captain discovers that Jim is an investigator, he pleads with Jim to find the killer before they dock in Liverpool in six days, or there could be international consequences. Aboard the beleaguered luxury liner are a thousand suspects, but no witnesses to the locked-cabin crime. Jim would prefer to keep Diana safely out of his investigation, but he's doubled over, seasick. Plus, Jim knows Diana can navigate the high society world of the ship's first-class passengers in ways he cannot. Together, using the tricks gleaned from their favorite fictional sleuth, Sherlock Holmes, Jim and Diana must learn why one man's life came to a murderous end"--.
new book 2023 fall.
Keywords: Historical fiction; Own voices; Mystery and detective stories; Detective and mystery fiction; Novels; Detective fiction; Mystery fiction